Enzymatic synthesis of 2-phenethyl acetate in water catalyzed by an immobilized acyltransferase from Mycobacterium smegmatis. Issue 4 (14th January 2022) - Li, Huan; Qin, Feng; Huang, Lijuan; Jia, Wenjing; Zhang, Mingliang; Li, Xin; Shu, Zhengyu
Abstract : Although water is an ideal green solvent for organic synthesis, it is difficult for most biocatalysts to carry out transesterification reactions in water because of the reversible hydrolysis reaction. Abstract : Although water is an ideal green solvent for organic synthesis, it is difficult for most biocatalysts to carry out transesterification reactions in water because of the reversible hydrolysis reaction. 3D structural characteristics and the microenvironment of an enzyme has an important effect on its selectivity for the transesterification reaction over the hydrolysis reaction. A novel 2-phenethyl acetate synthesis technology was developed using acyltransferase (EC 3.1.1.2) from Mycobacterium smegmatis (MsAcT) in water. Firstly, MsAcT was entrapped in a tetramethoxysilane gel network and the immobilization process of MsAcT increased its selectivity for the transesterification reaction over the hydrolysis reaction by 6.33-fold. Then, the synthesis technology of 2-phenethyl acetate using the immobilized MsAcT in water was optimized as follows: vinyl acetate was used as acyl donor, the molar ratio of vinyl acetate to 2-phenylethyl alcohol was 2 : 1, and the water content was 80% (w/w). The reaction was carried out at 40 °C for 30 min and conversion rate reached 99.17%. The immobilized MsAcT could be recycled for 10 batches. The synthesis method of 2-phenethyl acetate using MsAcT as a biocatalyst in water is a prospective green process technology.